Boas práticas na negociação de transferência de tecnologia entre NIT UFMA e empresas - MENDES, Raffira Marla Ferreira (2024)
Technology transfer plays an essential role in economic growth and global technological advancement, contributing to the diffusion of innovations and benefiting sustainability in various sectors. Innovation Law No. 10,973/2004 provides specific legal regulations regarding intellectual property and technological transfer, facilitating the intensification of these processes. The objective of this study is to identify technology transfer methods through a prospective study on university technology contracts and their respective modalities. Develop a proposal for a manual of good management practices for the NIT-UFMA technology transfer process. For this purpose, it was necessary to map technology contracts from assigning universities and their respective modalities, as well as analyze the contracts, identify the characteristics of the protected technology, process flow and negotiation, finally preparing the manual of good practices in management technology transfer. The methodology for developing this research is bibliographic, analysis of technology transfer contracts using the National Institute of Industrial Property - INPI database. Therefore, it is a documentary and applied analysis, whose focus is quantitative and qualitative. The number of 89 technology transfer contracts registered with INPI relating to universities was analyzed, percentage of endorsement, category, number of records by countries, states and universities, as well as the methods used to carry out technology transfer, difficulties in the process and best practices aimed at solving possible problems. In this way, the results refer to the preparation of the manual of good practices, identifying the appropriate methods for the proposal for negotiation and management of technology transfer agreements, making it possible to infer that the development of the project will bring gains to UFMA's NIT.